IMPROVING THE LITERAL READING COMPREHENSION USING READING CONTEXTUAL INTERNET-BASED INSTRUCTIONAL MATERIALS - Yuliyanti, Sri Ashara; Syam, Ummi Khaerati; Sujariati (English Language Teaching Methodology, 2024)
This study intends to determine whether reading contextual internet-based instructional materials can help third-grade students at UPTD SMPN 10 Barru.With their literal understanding. Two cycles of classroom action research were used in the design of this study. Eight meetings made up each cycle. There were four meetings per cycle. The third graders at UPTD SMPN 10 Barru kab. Barru participated in this classroom action research during the 2022–2023 school year. The 27 students in class IX who made up the research subjects were used. The application evaluated their reading comprehension.The student's reading comprehension in cycles I and II increased in terms of various scores. At the conclusion of the second cycle, the kids showed improvement. According to the study's conclusions, using contextual internet-based instructional materials could help students' reading comprehension. Mean scores for students' literal comprehension of the major idea on the D-Test were 37,04, 57,41, and 87,96 respectively, whereas the mean scores for students' literal comprehension of the supporting idea on the D-Test were 55,56, 58,33, and 85,19 respectively. The study's conclusions showed that students' literal comprehension improved when contextual internet-based instructional materials were used.